From dead to worse - Harris, Charlaine (New York : Ace Books, 2009)
After Hurricane Katrina and the manmade explosion at the vampire summit in New Orleans, Sookie Stackhouse faces danger, death, and, once again, betrayal by someone she loves.
Includes excerpt: Dead and gone (p. [307]-321).
Keywords: Stackhouse, Sookie (Fictitious character) -- Fiction; Vampires -- Fiction; Supernatural -- Fiction; Louisiana -- Fiction; Occult fiction; Mystery fiction